Perancangan aplikasi survei kepuasan layanan infrastruktur ti berbasis web menggunakan framework codeigniter 3 pada Direktorat Infrastruktur Teknologi Informasi BKN - Madhumita, J. Ryan; Zulhalim, Zulhalim; Sianipar, Anton Zulkarnain (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The goal of every service provided by a government or private agency, organization, or company, of course, is to offer the best possible service to its customers. Non-ministerial government organizations such as the BKN IT Infrastructure Directorate must ensure that they provide the best service to all work units and employees within the State Civil Service Agency. Therefore, it is necessary to monitor the quality of services that have been provided. One method is to carry out an IT infrastructure service satisfaction survey. Currently, the BKN Information Technology Infrastructure Directorate has conducted a customer satisfaction survey. However, the process still uses the conventional method, which starts from informing the survey and completing the data to the process of making reports which are done manually. This research was carried out by searching for theories and journals related to satisfaction ratings. System design is carried out using the Codeigniter 3 Framework combined with the Extreme Programming (XP) system development method where this development method is suitable for application in government agencies and places where there are few application developers. By using the CodeIgniter 3 Framework and the XP development method, it is hoped that the development of this application will run smoothly and quickly so that the application can be implemented immediately.